Reliability of health‐related physical fitness tests in adolescents: the MOVE Program. (16th October 2014) - Vanhelst, Jérémy; Béghin, Laurent; Fardy, Paul S.; Ulmer, Zekya; Czaplicki, Grégory
Summary: The aim was to examine the reliability of health‐related physical fitness tests that were used in a French health promotion program 'Move…A priority for your health'. Participants were 174 French youth (88 children and 86 adolescents) aged 8·2–16·2 years. Aerobic fitness, muscular strength, speed and flexibility were tested using 20‐m shuttle run test, ½ mile run test, basketball throw, standing long jump, shoulder stretch and 20/30/50‐m sprint tests. Reliability was calculated for the basketball throw, standing long jump, shoulder stretch and sprint tests. The tests were performed two times, 1 week apart on the same day of the week. Reliability was examined with intraclass correlation coefficients (ICCs) and Bland–Altman analysis. With the exception of the ½ mile run test, which resulted in moderate agreement (0·66), all tests had high reliability. ICCs were 0·97, 0·93, 0·91 and 0·93 for the sprint test, basketball throw, shoulder stretch and the standing long jump, respectively. The differences obtained between the first and the second trial were non‐significant. Results from this study indicate that the BOUGE health‐related physical fitness battery, administrated by physical education teachers, was reliable for measuring health‐related components of fitness in children and adolescents in a school setting.